Are integrins and ligands correlated at pig placental interface during pregnancy? - Velez Carolina; Clauzure Mariangeles; Williamson Delia; Garcia Monica; Koncurat Mirta; Barbeito Claudio (Bioscientifica, 2023)
In the present work, we emphasize the studies about integrins and their receptors in pig placental interface at different times of gestation. Uterine placental interface (n = 24) of 17, 30, 60 and 70 days of gestation (dg) and non-pregnant uterus (n = 4) of crossbred sows were used. The presence of αvβ3 (ITGAV (integrin subunit alpha V) ITGB3 (integrin subunit beta 3)) and α5β1 (ITGA5 (integrin subunit alpha V) ITGB3 (integrin subunit beta 3)) integrins, and their ligands fibronectin (FN) and osteopontin (OPN/ SPP1), was detected by immunohistochemistry, and the immunolabeled area percentage (IAP) and the optical density (OD) were determined. The integrins and its ligands analyzed have presented peaks of expression in early and mid-gestation, both in IAP and in the OD area, decreasing at 70 dg. These temporal changes showed us that the molecules studied in this work participate in embryo/feto-maternal attachment, variably. Besides, we found a significant correlation both in the intensity and in the extension of immunostaining for trophoblastic FN and endometrial αvβ3, and trophoblastic OPN and endometrial α5β1, throughout the entire pig pregnancy. At late gestation, there is notable placental remodeling with subsequent removal or renewal of folds at the uterine-placental interface that results in the loss of focal adhesions. The decrease of the expression of some integrins and their ligands in late gestation, particularly at 70 dg, would demonstrate that there would be other adhesion molecules and other ligands that could be participating in the establishment of the maternal-fetal interface.